(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Role of training and management development programs have been discussed by several authors. The contemporary world has so many changes in businesses. It would be meaningful to study the impact of training and MDP on employees. So, researchers have selected the employees of telecom sector. The study is based on a survey of 500 employees of BSNL and Airtel in the Delhi NCR region. The research questionnaire consisted 30 items. The key factors explored were Training and MDP, Job satisfaction, Employees’ performances, and employees’ self efficacy. The research suggested that training and MDP has significant positive impact on employees.